2020
DOI: 10.1021/acs.jctc.9b01146
|View full text |Cite
|
Sign up to set email alerts
|

Confinement and Crowding Effects on Folding of a Multidomain Y-Family DNA Polymerase

Abstract: Proteins in vivo endure highly various interactions from the luxuriant surrounding macromolecular cosolutes. Confinement and macromolecular crowding are the two major effects that should be considered while comparing the results of protein dynamics from in vitro to in vivo. However, efforts have been largely focused on single domain protein folding up to now, and the quantifications of the in vivo effects in terms of confinements and crowders on modulating the structure and dynamics as well as the physical und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 106 publications
4
19
0
Order By: Relevance
“…Stopped-flow Förster resonance energy transfer (FRET) studies monitoring intradomain ( Raper and Suo, 2016 ) and interdomain ( Xu et al, 2009 ; Maxwell et al, 2014 ) conformational dynamics of DPO4 during DNA binding as well as nucleotide binding and incorporation revealed weak and strong interactions between and within each domain of DPO4, respectively. Using only topological information, an SBM with homogeneously weighted native contacts predicted a ‘divide-and-conquer’ domain-wise folding scenario for DPO4 folding ( Wang et al, 2012a ; Chu et al, 2020 ). These results suggested that domains in DPO4 can fold without any aid from other domains.…”
Section: Discussionmentioning
confidence: 99%
“…Stopped-flow Förster resonance energy transfer (FRET) studies monitoring intradomain ( Raper and Suo, 2016 ) and interdomain ( Xu et al, 2009 ; Maxwell et al, 2014 ) conformational dynamics of DPO4 during DNA binding as well as nucleotide binding and incorporation revealed weak and strong interactions between and within each domain of DPO4, respectively. Using only topological information, an SBM with homogeneously weighted native contacts predicted a ‘divide-and-conquer’ domain-wise folding scenario for DPO4 folding ( Wang et al, 2012a ; Chu et al, 2020 ). These results suggested that domains in DPO4 can fold without any aid from other domains.…”
Section: Discussionmentioning
confidence: 99%
“…While there is enough evidence to confirm that confinement and crowding can significantly impact protein properties, it is not yet clear if they function similarly or differently to replicate in vivo cell environments [ 14 , 19 , 41 ]. Furthermore, only a few studies have explored the combined effects of confinement and crowding, an additional complexity that may arise due to the heterogeneous mixture of differently sized biomacromolecules, typical of native cellular environments [ 17 , 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…We hope this study will provide a foundation to create more relevant models for the in vitro investigation of protein behavior and fates in vivo. Such models may enable exploration of the mechanisms of multidomain protein folding and protein association and interactions, or to develop systems for drug delivery or implantable biosensors [ 26 , 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations